2010
DOI: 10.1186/1756-3305-3-120
|View full text |Cite
|
Sign up to set email alerts
|

High coverage of mass drug administration for lymphatic filariasis in rural and non-rural settings in the Western Area, Sierra Leone

Abstract: BackgroundLymphatic filariasis elimination programs are based upon preventative chemotherapy annually in populations with prevalence more than or equal to 1%. The goal is to treat 80% of the eligible, at risk population yearly, for at least 5 years, in order to interrupt transmission and prevent children from becoming infected. This level of coverage has been a challenge in urban settings. Assessing the coverage in a rapidly growing urban/non-rural setting with inadequate population data is also problematic. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 9 publications
1
73
0
Order By: Relevance
“…Richards et al, 2011 [36]/Nigeria/not statedLF programme reportSample was not stated (Rural and Urban setting) Plateau and Nasarawa states.To report on our 12-year effort to eliminate LF in Plateau and Nasarawa states, which was the first LF elimination effort to be launched in Nigeria.MDA for LF treatment in urban areas cannot rely on community volunteers and traditional leadership structures.In urban areas, rather than house to house, treatments were organized in central locations that served as distribution posts, commonly near a neighborhood church, mosque, health clinic or hospitalCommunity participation and coverage13. Hodges el al, 2010 [22]/Sierra Leone/2010Cross sectional study9249 participants were interviewed(Urban and rural setting).Freetown.To report the implementation strategy, social mobilization, the high coverage achieved in the urban western area and rural western area of Freetown, and the relative cost needed for each person treated during an MDA for LF.Key elements of success for social mobilization and implementation strategy (use of pretested IEC materials including FAQs, radio phone-ins, mobile texts, expert contact and government key stakeholder buy-in).Describes the independent monitoring used to estimate final coverage in this urban/non-rural setting where the current population size is uncertain.Suggests an implementation strategy and independent monitoring tool that could be useful in similar, rapidly growing cities implementing lymphatic filariasis elimination programmesCommunity participation, coverage and programme sustainability14. Malecela et al, 2009 [43]/ Tanzania/ 2000–2009LF elimination programme reportNationalTo report on the progress made by the Tanzania LF elimination programme.Establishment of morbidity management programme helped to alleviate patient suffering, reduce social stigma and community support for MDA for LF.Community participation and programme sustainability15.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Richards et al, 2011 [36]/Nigeria/not statedLF programme reportSample was not stated (Rural and Urban setting) Plateau and Nasarawa states.To report on our 12-year effort to eliminate LF in Plateau and Nasarawa states, which was the first LF elimination effort to be launched in Nigeria.MDA for LF treatment in urban areas cannot rely on community volunteers and traditional leadership structures.In urban areas, rather than house to house, treatments were organized in central locations that served as distribution posts, commonly near a neighborhood church, mosque, health clinic or hospitalCommunity participation and coverage13. Hodges el al, 2010 [22]/Sierra Leone/2010Cross sectional study9249 participants were interviewed(Urban and rural setting).Freetown.To report the implementation strategy, social mobilization, the high coverage achieved in the urban western area and rural western area of Freetown, and the relative cost needed for each person treated during an MDA for LF.Key elements of success for social mobilization and implementation strategy (use of pretested IEC materials including FAQs, radio phone-ins, mobile texts, expert contact and government key stakeholder buy-in).Describes the independent monitoring used to estimate final coverage in this urban/non-rural setting where the current population size is uncertain.Suggests an implementation strategy and independent monitoring tool that could be useful in similar, rapidly growing cities implementing lymphatic filariasis elimination programmesCommunity participation, coverage and programme sustainability14. Malecela et al, 2009 [43]/ Tanzania/ 2000–2009LF elimination programme reportNationalTo report on the progress made by the Tanzania LF elimination programme.Establishment of morbidity management programme helped to alleviate patient suffering, reduce social stigma and community support for MDA for LF.Community participation and programme sustainability15.…”
Section: Resultsmentioning
confidence: 99%
“…West and East AfricaGhana, Kenya, Mali, Nigeria, Sierra Leone and TanzaniaInvolvement of key health systems representatives and local leaders in health education. ( n  = 7) [22, 23, 25, 34, 36, 37, 41]. West and East AfricaGhana, Kenya, Mali, Sierra Leone and Tanzania.Selection, training and financial incentives provided to CDDs ( n  = 5) [22, 25, 34, 35, 37, 45], and provision of mobile phones and other forms of motivation [45] ( n  = 1) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 34 studies identified in our review, only 8 referred explicitly to eradication (yaws) or elimination (LF, onchocerciasis) as a programme objective. [11][15][16][17][18][19][20][21] Only one of those directly compared the costs of control and elimination strategies (for onchocerciasis), involving annual and biannual (twice yearly) mass treatment respectively; the difference is determined by the number of rounds rather than by so-called “last mile” costs. [21]…”
Section: Discussionmentioning
confidence: 99%